Sensitivity of Visual System in 5-Day “Dry” Immersion With High-Frequency Electromyostimulation - Shoshina, Irina; Zelenskaya, Inna; Karpinskaia, Valeriia; Shilov, Yuri; Tomilovskaya, Elena (Frontiers in Neural Circuits, 2021)
The aim of this work was to study the sensitivity of the visual system in 5-day "dry" immersion with a course of high-frequency electromyostimulation (HFEMS) and without it. "Dry" immersion (DI) is one of the most effective models of microgravity. DI reproduces three basic effects of weightlessness: physical inactivity, support withdrawal and elimination of the vertical vascular gradient. The "dry" immersion included in the use of special waterproof and highly elastic fabric on of immersion in a liquid similar in density to the tissues of the human body. The sensitivity of the visual system was assessed by measuring contrast sensitivity and magnitude of the Müller-Lyer illusion. The visual contrast sensitivity was measured in the spatial frequency range from 0.4 to 10.0 cycles/degree. The strength of visual illusion was assessed by means of motor response using “tracking”. Measurements were carried out before the start of immersion, on the 1st, 3rd, 5th days of DI, and after its completion. Under conditions of "dry" immersion without HFEMS, upon the transition from gravity to microgravity conditions (BG and DI1) we observed significant differences in contrast sensitivity in the low spatial frequency range, whereas in the experiment with HFEMS – in the medium spatial frequency range. In the experiment without HFEMS, the Müller-Lyer illusion in microgravity conditions was absent, while in the experiment using HFEMS it was significantly above zero at all stages. Thus, we obtained only limited evidence in favor of the hypothesis of a possible compensating effect of HFEMS on changes in visual sensitivity upon the transition from gravity to microgravity conditions and vice versa. The study is a pilot and requires further research on the effect of HFEMS on visual sensitivity.